The effect of emotion regulation difficulties and loneliness on anxiety, depression, and stress levels in remote workers - Ulaş Korkmaz; Meltem Hazel Şimşek; Ömer Faruk Şahin (BMC Public Health)
Abstract Background While remote work brings flexibility to work life, it can also bring loneliness, emotion regulation difficulties, and some mental health symptoms. This study examined the relationship between loneliness and emotion regulation difficulties and levels of depression, anxiety, and stress in remote workers and the role of some sociodemographic variables in these relationships. Methods An analytical cross-sectional observational study was conducted. One hundred twenty-one participants (53.7% female, 46.3% male), aged 23–56 and working remotely for at least six months, were reached through snowball sampling and evaluated using online survey forms. Data were collected using a sociodemographic information form, the UCLA Loneliness Scale, the Depression Anxiety Stress Scale, and the Difficulties in Emotion Regulation Scale. In addition to correlation analyses and group comparisons, mediation analyses were conducted using the bootstrap method. Results Emotion regulation difficulties and loneliness were significantly positively associated with depression, anxiety, and stress. An increase in the number of days working remotely per week increased anxiety levels, and emotion regulation difficulties mediated this effect. Loneliness had a mediating role in the relationship between emotion regulation difficulties and depression. Conclusions Emotion regulation difficulties and loneliness have a significant impact on symptoms of depression, anxiety, and stress in individuals working remotely. These findings support the need to strengthen emotion regulation skills and develop policies that increase social interaction to support the mental health of remote workers.